Vitrification of Human Embryos After Manipulation with Zona Pellucida - Yurchuk, Taisiia A.; Petrushko, Maryna P.; Piniaiev, Volodymyr I.; Buderatskaya, Natalya A. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 184